On the formation of the structure of the philosophy od education throughout the history of mankind (Journal of Philosophy Culture and Political Science, 2020)
The article is devoted to little-studied research and problems of the formation of the structure of the philosophy of education throughout the history of mankind. The development of philosophical systems and the philosophy of education since ancient times was, it would seem, spontaneous in nature, being formed under the influence of various philosophical, religious, moral and ethical teachings and currents.However, looking at a complex mechanism consisting of many similar systems, one can find some secretive control and manipulation of human civilization from ancient times to the present day with still unknown and unexplored goals. This mechanism of pedagogical influence on people, in fact, is a complex of fundamental tools, which could be played by myths and legends of ancient peoples, scriptures, worldreligions, philosophical systems, etc. The main purpose of the article is, if not direct, then at least indirect evidence of a certain control of humanity with the help of inferential methods and assumptions. Inductive and deductive methods are most suitable for this purpose. How these methods can be effectively used is described in the article. These methods allow you to come to the results and conclusions, basedon the discovered facts, artifacts and direct evidence. The work is scientific and theoretical in nature and enters into the orbit of fundamental research on this global topic.Key words: philosophy and pedagogy of hidden influence, Program for the development of mankind, inductive and deductive research methods, myths, legends and writings of ancient peoples.